2010
DOI: 10.1007/s11356-010-0397-9
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls and organochlorinated pesticides in birds from a contaminated region in South China: association with trophic level, tissue distribution and risk assessment

Abstract: Purpose Birds have been used successfully for biomonitoring of the levels and effects of persistent organic pollutants (POPs) in the environments; however, there is exceedingly little data on organochlorinated pesticide (OCPs) and polychlorinated biphenyls (PCBs) residues in bird inhabiting in China. In the present study, we detected the concentrations of PCBs, dichlorodiphenyltrichloroethane and its metabolites (DDTs) and hexachlorocyclohexanes (HCHs) in muscle, liver and kidney of birds that inhabit in an e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 43 publications
(45 reference statements)
2
10
2
Order By: Relevance
“…The highest PCB concentration was observed in the e-waste recycling area, suggesting that e-waste is 31, 52, 60, 66, 74, 99, 101, 105, 115/87, 118, 128, 130, 137, 138, 146, 149/139, 153, 156, 158, 164/163, 171, 172, 175, 180, 183, 187, 190, 191, 194, 195, 203, 205, 206, and one of the important sources of PCBs in the study site. Previous studies have also reported that much higher PCB concentrations were detected in aquatic biota such as waterbirds, fish, and hydrobiidae at the same sampling site (Luo et al, 2009;Zhang et al, 2010Zhang et al, , 2011. These results indicate that higher PCB levels in biota from Guangdong Province could be linked to high density of e-waste recycling activities in this region.…”
Section: Pcb and Ddt Levelssupporting
confidence: 61%
“…The highest PCB concentration was observed in the e-waste recycling area, suggesting that e-waste is 31, 52, 60, 66, 74, 99, 101, 105, 115/87, 118, 128, 130, 137, 138, 146, 149/139, 153, 156, 158, 164/163, 171, 172, 175, 180, 183, 187, 190, 191, 194, 195, 203, 205, 206, and one of the important sources of PCBs in the study site. Previous studies have also reported that much higher PCB concentrations were detected in aquatic biota such as waterbirds, fish, and hydrobiidae at the same sampling site (Luo et al, 2009;Zhang et al, 2010Zhang et al, , 2011. These results indicate that higher PCB levels in biota from Guangdong Province could be linked to high density of e-waste recycling activities in this region.…”
Section: Pcb and Ddt Levelssupporting
confidence: 61%
“…2a). Data for OCP concentrations in these three birds from other areas are scarce; however, as shown in Table 3, the OCP concentrations in the birds in this study were comparable to those in omnivorous birds from other regions (Dhananjayan et al 2011;Zhang et al 2011). Conversely, the OCP levels in these studied birds were lower than those reported Fig.…”
Section: Accumulation Of Ocps In Terrestrial Faunacontrasting
confidence: 45%
“…Additionally, high concentrations of OCP residues in soils can be volatilized and subsequently enter into vegetation or animals through the air. Moreover, multiclass plants can easily absorb and accumulate OCPs from soils directly, and terrestrial animals may bioaccumulate OCPs through food chains (Dhananjayan et al 2011;Zhang et al 2011). As a result, vegetation and terrestrial animals around pesticide factories may be at risks.…”
Section: Introductionmentioning
confidence: 99%
“…This includes several endangered species, such as black stork (Ciconia nigra) and black-necked crane (Grus nigricollis). Contamination of the lake by POPs could pose potential health risks to the birds (Fisk et al, 2001;Lam et al, 2008;Zhang et al, 2011). Few studies have been performed to investigate POPs in the Qinghai Lake area.…”
Section: Introductionmentioning
confidence: 99%